Analysis of strength on the thick plate part using response surface methodology - Zamri Razali (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is about research on the analysis of strength on the thick plate (thickness of the part is more than 3mm) using response surface methodology (RSM). The objective of this project is to improve the mechanical strength of the thick plate part from the significant parameter by using RSM. To find the significant factor for this research, the previous journal from other researcher were reviewed and has been conclude that melt temperature and mould temperature were the significant factor.